JESD 2019
DOI: 10.7176/jesd/10-6-13
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effect of Competitive Business Strategy on Corporate Environmental Performance and Corporate Carbon Emission Disclosure Towards Corporate Financial Performance

Abstract: The purpose of this research is to examine the effect of corporate environmental performance and corporate carbon emission disclosure toward corporate financial performance with competitive business strategy as moderating variable. The research design is quantitative methods using secondary data, which is data from the sustainability report of 18 go public companies listed on the Indonesia stock exchange from 2015 to 2017, with 54 units of analysis for the period of 2015-2017. The data analysis used in this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Based on the results of the data test in Table8, the prob>f result is 0.0000, which means that this number is smaller than the constant value of 0.05, Disclosure; this is evidenced by the results of the coefficient of determination test where the coefficient value of the ComBusStra variable is 0.0378854.From the results of the test of the coefficient of determination, it can be concluded that every increase of 1 ComBusStra unit will increase CED by 0.0378854. This is similar to research conducted byRusli et al (2019), which proves that Competitive Business Strategy cannot moderate the relationship between Corporate Carbon Emission Disclosure and Corporate Financial Performance.The ComBusStra variable is also not in line with stakeholder theory, which means that there is no emphasis on companies running CED by carrying out a good competitive strategy. Companies prefer to increase sales rather than fulfill stakeholder requests to disclose CED.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Based on the results of the data test in Table8, the prob>f result is 0.0000, which means that this number is smaller than the constant value of 0.05, Disclosure; this is evidenced by the results of the coefficient of determination test where the coefficient value of the ComBusStra variable is 0.0378854.From the results of the test of the coefficient of determination, it can be concluded that every increase of 1 ComBusStra unit will increase CED by 0.0378854. This is similar to research conducted byRusli et al (2019), which proves that Competitive Business Strategy cannot moderate the relationship between Corporate Carbon Emission Disclosure and Corporate Financial Performance.The ComBusStra variable is also not in line with stakeholder theory, which means that there is no emphasis on companies running CED by carrying out a good competitive strategy. Companies prefer to increase sales rather than fulfill stakeholder requests to disclose CED.…”
supporting
confidence: 87%
“…Several studies analyzing the effect of disclosing company carbon emissions on company financial performance conducted by Al-Rdaydeh (2018) stated that a competitive business strategy strengthens the influence between the company's environmental performance and the company's financial performance. However, Rusli et al (2019)…”
Section: Literature Reviewmentioning
confidence: 99%
“…The theoretical framework for social responsibility disclosure is based on stakeholder theory and institutional theory. Stakeholder theory explains that companies need to have benefits for stakeholders besides the entity operating for its interests [3,55]. Thus, the company certainly needs to carry out social activities and provide this information to its stakeholders as a form of corporate responsibility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Global warming is the main problem of climate change caused by human activities such as burning fossil fuels and oil, which causes carbon dioxide in the atmosphere [1]. Therefore, global warming has become an increasing political and trade issue vital for most countries [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Hossain et al (2017) support stakeholder theories that Boards of Directors serve as a liaison mechanism between enterprises and their stakeholders, as well as providing legitimacy to diverse stakeholder groups in society. Then, based on the legitimacy theory, the firm will focus on its relationship with society through regulations made by the government (Rusli et al, 2019).…”
Section: Introductionmentioning
confidence: 99%